2017
DOI: 10.1002/rmv.1958
|View full text |Cite
|
Sign up to set email alerts
|

Criteria to define interruption of transmission of human cytomegalovirus from organ donor to recipient

Abstract: SummaryIn this review article, we consider results suggesting that transmission of human cytomegalovirus (HCMV) from a donor of a solid organ to an immunologically naive individual can be reduced. Two randomized controlled trials have been conducted recently, one of active immunization of recipients pretransplant and another of passive immunization with monoclonal antibodies specific for HCMV given at the time of transplant. Although the available data are encouraging-providing evidence of a reduction in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Human Cytomegalovirus (HCMV) infection is common, with seroprevalence ranging from 60 to 100% (1). HCMV can promote substantial mortality and morbidity in immunocompromised individuals, including solid organ transplant (SOT) recipients (2). In these patients, CMV end-organ disease results from primary infection, reinfection or reactivation (3).…”
mentioning
confidence: 99%
“…Human Cytomegalovirus (HCMV) infection is common, with seroprevalence ranging from 60 to 100% (1). HCMV can promote substantial mortality and morbidity in immunocompromised individuals, including solid organ transplant (SOT) recipients (2). In these patients, CMV end-organ disease results from primary infection, reinfection or reactivation (3).…”
mentioning
confidence: 99%
“…Compared to recipients of placebo, the vaccine did not reduce the incidence of infection or end-organ disease, but did reduce the severity of disease. Measures of viral load were not available in those days but, because natural history studies show a strong correlation between a high viral load and the development of end-organ disease, it is very likely that this vaccine had its beneficial clinical effects by reducing viral loads post-transplant (3,4,18). In 2011, our group reported that administration of a vaccine based on theCMV glycoprotein B plus MF59 adjuvant reduced parameters of viral load and the correlate of protection was the titre of antibodies made against glycoprotein B.…”
mentioning
confidence: 99%
“…It will be important to determine if prophylaxis with drugs other than valganciclovir, eg, letermovir, have the same effect after solid organ transplant. They also provide valuable information on which immune responses may be protective against CMV posttransplant, thereby providing a target for novel vaccines to aim for if we wish them to protect transplant patients . Finally, they draw attention to the fact that the risk borne by CMV seronegative recipients can be reduced if they mount an effective immune response against this virus and should encourage the conduct of more randomised controlled trials to give prototype CMV vaccines pretransplant as a way of controlling CMV viral load post‐transplant .…”
mentioning
confidence: 99%
“…They also provide valuable information on which immune responses may be protective against CMV posttransplant, thereby providing a target for novel vaccines to aim for if we wish them to protect transplant patients . Finally, they draw attention to the fact that the risk borne by CMV seronegative recipients can be reduced if they mount an effective immune response against this virus and should encourage the conduct of more randomised controlled trials to give prototype CMV vaccines pretransplant as a way of controlling CMV viral load post‐transplant . A new phase 2 randomised controlled trial is currently underway in renal transplant patients with a novel vaccine based on a backbone of lymphocytic choriomeningitis virus and the results are awaited with interest (NCT03629080).…”
mentioning
confidence: 99%